Preparation method of sponge implant with rapid and long-term analgesic, anti-inflammatory, antipyretic and wound healing promoting effects

By using small and medium molecular weight prototype aminoglycans in the implant, combined with materials such as diclofenac, hirudin and hydroxypropyl cellulose, a spongy implant agent was prepared, which solved the problem of short duration of the drug and major side effects. , achieves rapid and long-term analgesic, anti-inflammatory, antipyretic and wound healing effects, significantly improving the stability and safety of the drug.

CN119235748APending Publication Date: 2025-01-03RUNMEI TIME (BEIJING) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411334473.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

During use, existing implants may cause pain, discomfort, local reactions and systemic adverse reactions, and the efficacy lasts for a short time, making it difficult to achieve rapid and long-term analgesic, anti-inflammatory, antipyretic and wound healing effects. .

Method used

The salt or complex formed by small and medium molecular weight prototype aminoglycans and diclofenac and hirudin are used to combine hydroxypropyl cellulose and crosslinked sodium hyaluronate to prepare a sponge-like implant agent through freeze-drying to achieve the sustained release effect of the drug. , prolong the analgesic, anti-inflammatory, and antipyretic effects and promote wound healing.

Benefits of technology

It achieves rapid and long-term analgesic, anti-inflammatory and antipyretic effects, reduces the incidence of side effects, improves the stability and salt tolerance of the drug, avoids serious side effects caused by the rapid release of the drug, and significantly improves the wound healing effect. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a sponge implant. The method comprises the following steps: 1) dispersing prototype amino chitosan with small molecular weight, prototype amino chitosan with medium molecular weight and hydroxy propyl cellulose with the molecular weight of about 100,000-200,000 Daltons into water; adding nano-scale powder of prototype diclofenac and hirudin or a water dispersion liquid of the nano-scale powder of prototype diclofenac and hirudin; the diclofenac sodium and the hirudin are added; cross-linked sodium hyaluronate is added; respectively adding an aqueous solution of collagen and an aqueous solution of heme peroxidase, so that the collagen is basically crosslinked; and freezing and drying in a container to remove the solvent. The sponge implant has the effects of rapidly easing pain for a long time, diminishing inflammation, relieving fever and promoting wound healing; the stability is good, and salt resistance and high ion strength resistance are realized; 'dumping 'is avoided; the occurrence rate of side effects is lower, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A method for preparing an implant, in particular, a method for preparing a sponge implant which has rapid and long-term analgesic, anti-inflammatory and antipyretic effects and can promote wound healing. Technical Background

[0002] Implants are sterile solid preparations with a long release period, and can maintain stable release of drugs, reduce the toxic and side effects of drugs and other advantages. However, implant preparations also have some disadvantages, such as the need for surgical implantation, which may cause pain and discomfort, such as local reactions such as redness, swelling, edema, lumps, itching, and discomfort at the implant site; some irritants may prolong the duration of these adverse reactions, such as excessive exposure to sunlight, overheating, drinking, improper use of cosmetics and skin care products, etc. A small number of patients will have local allergic reactions to this product, resulting in redness, swelling, nodules, urticaria and other reactions, most of which can be relieved within one month; some patients may cause inflammation, cyst formation, suppuration reaction, and in severe cases, scar tissue may form, and wound infection may also occur. Patients may also experience systemic adverse reactions, which include: cold-like symptoms (such as fever, headache, neuralgia, muscle pain, nausea, physical discomfort, dizziness), itching, skin rash, tingling, numbness, temporary blurred vision, temporary polyarticular pain and systemic immune diseases.

[0003] If the patient experiences the above adverse reactions, appropriate drug treatment is required, as the above adverse reactions last for a long time.

[0004] Therefore, there is a need to prepare an implant that has rapid and long-term analgesic, anti-inflammatory and antipyretic effects and can promote wound healing. Summary of the invention

[0005] Diclofenac sodium is a non-steroidal anti-inflammatory drug with significant analgesic, anti-inflammatory and antipyretic effects. It produces analgesic, anti-inflammatory and antipyretic effects by inhibiting cyclooxygenase and blocking the synthesis of prostaglandins. Its effect is 2-2.5 times stronger than indomethacin and 26-50 times stronger than acetylsalicylic acid. It is characterized by strong efficacy, mild adverse reactions, small dosage and small individual differences. The drug has a plasma protein binding rate of 99.7%. The half-life is 1-2 hours. The daily dose is usually taken in 2-3 times. Therefore, the goals of analgesia, anti-inflammatory and antipyretic can be achieved.

[0006] Hirudin has the main effects and functions of anti-thrombosis and promoting wound recovery. Hirudin can inhibit the binding of thrombin to platelets and the release of thrombin, thereby binding thrombin to fibrin, inducing the activation of coagulation factors and platelet reactions. Hirudin can prevent the coagulation of fibrinogen, inhibit platelet precipitation, prevent arterial and venous occlusion, prevent thrombosis after surgery, promote extracorporeal circulation, accelerate or strengthen the effects of drugs such as diclofenac / sodium, and promote wound healing.

[0007] Based on the above principles, the analgesic, anti-inflammatory and antipyretic effects can be achieved and the purpose of promoting wound healing can be achieved.

[0008] However, the duration of efficacy of diclofenac and hirudin is short and they need to be made into sustained-release preparations.

[0009] The present invention adopts salts (or complexes) formed by moderately small and medium molecular weight prototype aminopolysaccharides and prototype diclofenac and hirudin to delay the release of the drug, thereby achieving a longer-term analgesic, anti-inflammatory, antipyretic effect and promoting wound healing.

[0010] The present invention has been achieved based on the above findings.

[0011] The present invention relates to a method for preparing a sponge implant having rapid and long-term analgesic, anti-inflammatory, antipyretic and wound healing promoting effects, the method comprising:

[0012] 1) Dispersing a prototype amino chitosan with a small molecular weight, a prototype amino chitosan with a medium molecular weight, and a hydroxypropyl cellulose with a molecular weight of about 100,000-200,000 Daltons in water, wherein the prototype amino chitosan with a small molecular weight has a molecular weight of 1000-5000 Daltons, and its concentration is 10-20% wt / wt (based on 100% of the final total amount, i.e., 10-20 parts per 100 parts by weight), the prototype amino chitosan with a medium molecular weight has a molecular weight of 10000-50000 Daltons, and its concentration is 5-10% wt / wt (based on 100% of the final total amount, i.e., 5-10 parts per 100 parts by weight), and the hydroxypropyl cellulose has a concentration of 3-6% wt / wt (based on 100% of the final total amount, i.e., 3-6 parts per 100 parts by weight), to obtain liquid A;

[0013] 2) Adding prototype diclofenac and hirudin nanopowder or its aqueous dispersion to liquid A, wherein the (molar) amount of diclofenac is 0.95-1 times the (molar) amount of the amino group in the aminochitosan, and the weight ratio of the hirudin to the diclofenac is 1:50-200, mixing, and placing at room temperature for 12-24 hours to obtain liquid B;

[0014] 3) Add diclofenac sodium and hirudin to liquid B, wherein the weight of diclofenac sodium and hirudin is 0.3-0.8 times the weight of the above-mentioned prototype diclofenac and hirudin, respectively, and mix well to obtain liquid C;

[0015] 4) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 1-5% wt / wt (based on the final total amount of 100%, i.e., 1-5 parts per 100 parts by weight) to obtain liquid D;

[0016] 5) Adding an aqueous solution of collagen and an aqueous solution of heme peroxidase to liquid D respectively, wherein the concentration of the above collagen is 1-6% wt / wt (based on the final total amount of 100%, that is, 1-6 parts per 100 weight parts in the end), and the ratio of the amount of the above heme peroxidase to the above collagen is 1-15U / g. After mixing evenly, the temperature is maintained at 0°C to 4°C for 24-72 hours to make the collagen basically cross-linked, thereby obtaining liquid E;

[0017] 6) Liquid E is placed in a container so that the liquid layer thickness is 1-2 mm, and freeze-dried to remove the solvent. DETAILED DESCRIPTION

[0018] The hydroxypropyl cellulose is preferably selected from Klucel JF (whose molecular weight is about 140,000 Daltons and viscosity is 150-400 mPa·s at a concentration of 5% wt / wt.

[0019] The weight ratio of the hirudin to the diclofenac is preferably 1:80-150.

[0020] The concentration of the above-mentioned small molecular weight prototype amino polysaccharide is preferably 13-17% wt / wt.

[0021] The concentration of the above-mentioned prototype amino polysaccharide with medium molecular weight is preferably 6-8% wt / wt.

[0022] The concentration of the hydroxypropyl cellulose is preferably 4-5% wt / wt.

[0023] The molar amounts of the diclofenac and hirudin sodium are preferably 0.4-0.6 times the molar amounts of the prototype diclofenac and hirudin, respectively.

[0024] The concentration of the cross-linked sodium hyaluronate is preferably 2-4% wt / wt.

[0025] The concentration of the above collagen is preferably 3-4% wt / wt.

[0026] The ratio of the amount of the glutamyl endopeptidase to the amount of the collagen is preferably 3-10 U / g, more preferably 4-7 U / g.

[0027] The thickness of the liquid layer is preferably 1.3-1.8 mm.

[0028] The preparation method of the sponge implant of the present invention also comprises further preparing the sponge implant into a film, column, strip, plate, block, plug, pill, sheet, sponge or gel.

[0029] The present invention adopts salts (or complexes) formed by moderately small and medium molecular weight prototype amino polysaccharides and prototype prototype diclofenac and hirudin as the main sustained-release material and the main sustained-release mechanism. They can release prototype diclofenac and hirudin at two moderately different speeds, and can provide sustained-release effects at medium speeds and lower speeds, thereby achieving long-term analgesic, anti-inflammatory and antipyretic effects and promoting wound healing.

[0030] In the present invention, the salt (or complex) formed by the molecular weight prototype amino polysaccharide with lower or higher viscosity and the prototype diclofenac and hirudin releases diclofenac and hirudin too slowly (no or weak analgesic, anti-inflammatory, antipyretic effect, and wound healing effect) or too quickly (significant side effects), which cannot meet the requirements of the present invention.

[0031] The invention is simultaneously formulated with appropriate amounts of diclofenac sodium and hirudin to release diclofenac and hirudin at a conventional speed, thereby achieving the effects of analgesia, anti-inflammation, antipyretic and promoting wound healing at a relatively fast speed.

[0032] The present invention also uses medium viscosity hydroxypropyl cellulose and relatively high molecular weight cross-linked sodium hyaluronate as auxiliary sustained-release materials. The medium viscosity hydroxypropyl cellulose, relatively high molecular weight cross-linked sodium hyaluronate and cross-linked collagen are used to enhance the sustained-release effect and prolong the sustained-release time, thereby further prolonging the analgesic, anti-inflammatory and antipyretic effects and promoting the healing of wounds.

[0033] The functions of medium viscosity hydroxypropyl cellulose also include: 1) preventing the aggregation and precipitation of salts (or complexes) formed by prototype amino polysaccharides and prototype diclofenac and hirudin, especially in the presence of salt, especially in the state of high ionic strength;

[0034] 2) It can also prevent the aggregation and precipitation of high molecular weight cross-linked sodium hyaluronate and cross-linked collagen in the presence of salt, especially in high ionic strength conditions, especially in the presence of calcium salt and magnesium salt.

[0035] In the present invention, the hydroxypropyl cellulose with a lower viscosity has a poor blocking effect and is difficult to prevent aggregation and precipitation due to its low viscosity, and the above-mentioned effect cannot be achieved. The hydroxypropyl cellulose with a higher viscosity has a high viscosity and is not used in large amounts, and has a poor salt resistance effect and is also difficult to prevent aggregation and precipitation, and the above-mentioned effect cannot be achieved; in addition, due to its high viscosity, the operation is difficult or the process becomes complicated, for example, the above-mentioned room temperature placement time (i.e., the formation time of the salt (or complex) formed by the prototype amino polysaccharide and the prototype diclofenac, hirudin) is too long.

[0036] If hydroxypropyl cellulose fails to achieve the above-mentioned effects, it will affect the sustained-release effect, resulting in no or weak analgesic, anti-inflammatory, antipyretic, and wound healing effects, or the analgesic, anti-inflammatory, antipyretic, and wound healing effects are short-lived, making it difficult to achieve a longer period of analgesic, anti-inflammatory, antipyretic, and wound healing effects, and may even cause "pouring release" of diclofenac and hirudin, that is, a one-time rapid release, which may result in serious side effects.

[0037] The advantages of the present invention over the prior art are:

[0038] 1) It can relieve pain, reduce inflammation, reduce fever, and promote wound healing at a relatively fast speed, and it can also relieve pain, reduce inflammation, reduce fever, and promote wound healing for a relatively long time;

[0039] 2) Good stability, resistance to salt and high ionic strength;

[0040] 3) Not “pouring out”;

[0041] 4) Lower incidence of side effects.

[0042] Example

[0043] The following non-selective examples, i.e., methods for preparing implants, further describe preferred embodiments within the scope of the present invention. There are many variations of these embodiments within the scope of the present invention.

[0044] Example 1

[0045] 1) Dispersing a prototype amino chitosan with a small molecular weight, a prototype amino chitosan with a medium molecular weight, and hydroxypropyl cellulose Klucel JF with a molecular weight of about 120,000 Daltons in water, wherein the prototype amino chitosan with a small molecular weight has a molecular weight of 1000-5000 Daltons, and its concentration is 18% wt / wt (based on 100% of the final total amount, i.e., 18 parts per 100 parts by weight), the prototype amino chitosan with a medium molecular weight has a molecular weight of 10000-50000 Daltons, and its concentration is 8% wt / wt (based on 100% of the final total amount, i.e., 8 parts per 100 parts by weight), and the hydroxypropyl cellulose has a concentration of 4% wt / wt (based on 100% of the final total amount, i.e., 4 parts per 100 parts by weight), to obtain liquid A;

[0046] 2) Adding prototype diclofenac and nanometer-scale powder of hirudin or its aqueous dispersion to liquid A, wherein the (molar) amount of diclofenac is 0.98-1 times the (molar) amount of the amino group in the amino polysaccharide, and the weight ratio of the hirudin to the diclofenac is 1:100, mixing, and placing at room temperature for 12-24 hours to obtain liquid B;

[0047] 3) Add diclofenac sodium and hirudin to liquid B, wherein the weight of diclofenac sodium and hirudin is 0.5 times the weight of the above-mentioned prototype diclofenac and hirudin, respectively, and mix well to obtain liquid C;

[0048] 3) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 2% wt / wt (based on the final total amount of 100%, i.e., 2 parts per 100 parts by weight) to obtain liquid D;

[0049] 4) Adding an aqueous solution of collagen and an aqueous solution of heme peroxidase to liquid D respectively, wherein the concentration of the above collagen is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 weight parts in the end), and the ratio of the amount of the above heme peroxidase to the above collagen is 8 U / g. After mixing evenly, the temperature is maintained at 0°C to 4°C for 24-72 hours to make the collagen basically cross-linked, thereby obtaining liquid E;

[0050] 5) Liquid E was placed in a container so that the liquid layer thickness was 1.2 mm, and freeze-dried to remove the solvent.

[0051] Comparative Example 1-1

[0052] The prototype amino chitosan with a molecular weight of 1000-5000 Daltons in Example 1 was replaced with a prototype amino chitosan with a molecular weight of 100-500 Daltons, and the rest remained unchanged.

[0053] Comparative Example 1-2

[0054] The prototype amino chitosan with a molecular weight of 10,000-50,000 Daltons in Example 1 was replaced with a prototype amino chitosan with a molecular weight of 100,000-250,000 Daltons, and the rest remained unchanged.

[0055] Example 2

[0056] 1) Dispersing a prototype amino chitosan with a small molecular weight, a prototype amino chitosan with a medium molecular weight, and hydroxypropyl cellulose Klucel JF with a molecular weight of about 120,000 Daltons in water, wherein the prototype amino chitosan with a small molecular weight has a molecular weight of 1000-5000 Daltons, and its concentration is 14% wt / wt (based on 100% of the final total amount, i.e., 14 parts per 100 parts by weight), the prototype amino chitosan with a medium molecular weight has a molecular weight of 10000-50000 Daltons, and its concentration is 6% wt / wt (based on 100% of the final total amount, i.e., 6 parts per 100 parts by weight), and the hydroxypropyl cellulose has a concentration of 5% wt / wt (based on 100% of the final total amount, i.e., 5 parts per 100 parts by weight), to obtain liquid A;

[0057] 2) Adding prototype diclofenac and hirudin nanopowder or its aqueous dispersion to liquid A, wherein the (molar) amount of diclofenac is 0.98-1 times the (molar) amount of the amino group in the amino polysaccharide, and the weight ratio of the hirudin to the diclofenac is 1:80, mixing, and leaving at room temperature for 12-24 hours to obtain liquid B;

[0058] 3) Add diclofenac sodium and hirudin to liquid B, wherein the weight of diclofenac sodium and hirudin is 0.6 times the weight of the above-mentioned prototype diclofenac and hirudin, respectively, and mix well to obtain liquid C;

[0059] 3) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight) to obtain liquid D;

[0060] 4) Adding an aqueous solution of collagen and an aqueous solution of heme peroxidase to liquid D respectively, wherein the concentration of the above collagen is 2% wt / wt (based on the final total amount of 100%, that is, 2 parts are contained in every 100 weight parts), and the ratio of the amount of the above heme peroxidase to the above collagen is 5 U / g. After mixing evenly, the temperature is maintained at 0°C to 4°C for 24-72 hours to make the collagen basically cross-linked, thereby obtaining liquid E;

[0061] 5) Liquid E was placed in a container so that the liquid layer thickness was 1.5 mm, and freeze-dried to remove the solvent.

[0062] Comparative Example 2-1

[0063] 90% of the amount of the prototype amino chitosan with a molecular weight of 1000-5000 Dalton in Example 2 (ie, 10% of the original amount) was replaced with the prototype amino chitosan with a molecular weight of 10000-50000 Dalton, and the rest remained unchanged.

[0064] Comparative Example 2-2

[0065] 90% of the amount of the prototype amino chitosan with a molecular weight of 10000-50000 Dalton in Example 2 (ie, 10% of the original amount) was replaced with the prototype amino chitosan with a molecular weight of 1000-5000 Dalton, and the rest remained unchanged.

[0066] Example 3

[0067] 1) Dispersing a prototype amino chitosan with a small molecular weight, a prototype amino chitosan with a medium molecular weight, and hydroxypropyl cellulose Klucel JF with a molecular weight of about 120,000 Daltons in water, wherein the prototype amino chitosan with a small molecular weight has a molecular weight of 1000-5000 Daltons, and its concentration is 16% wt / wt (based on 100% of the final total amount, i.e., 16 parts per 100 parts by weight), the prototype amino chitosan with a medium molecular weight has a molecular weight of 10000-50000 Daltons, and its concentration is 8% wt / wt (based on 100% of the final total amount, i.e., 8 parts per 100 parts by weight), and the hydroxypropyl cellulose has a concentration of 4% wt / wt (based on 100% of the final total amount, i.e., 4 parts per 100 parts by weight), to obtain liquid A;

[0068] 2) Adding prototype diclofenac and nanometer-scale powder of hirudin or its aqueous dispersion to liquid A, wherein the (molar) amount of diclofenac is 0.98-1 times the (molar) amount of the amino group in the amino polysaccharide, and the weight ratio of the hirudin to the diclofenac is 1:150, mixing, and leaving at room temperature for 12-24 hours to obtain liquid B;

[0069] 3) Add diclofenac sodium and hirudin to liquid B, wherein the weight of diclofenac sodium and hirudin is 0.5 times the weight of the above-mentioned prototype diclofenac and hirudin, respectively, and mix well to obtain liquid C;

[0070] 3) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 1% wt / wt (based on the final total amount of 100%, i.e., 1 part per 100 parts by weight) to obtain liquid D;

[0071] 4) Adding an aqueous solution of collagen and an aqueous solution of heme peroxidase to liquid D respectively, wherein the concentration of the above collagen is 5% wt / wt (based on the final total amount of 100%, that is, 5 parts per 100 weight parts in the end), the ratio of the amount of the above heme peroxidase to the above collagen is 10U / g, and after mixing evenly, the temperature is maintained at 0°C to 4°C for 24-72 hours to allow the collagen to be basically cross-linked, thereby obtaining liquid E;

[0072] 5) Liquid E was placed in a container so that the liquid layer thickness was 1.4 mm, and freeze-dried to remove the solvent.

[0073] Comparative Example 3-1

[0074] The weight ratio of hirudin to diclofenac in Example 3 was changed from 1:150 to 0.01:150 (ie 1:15000), and the other factors remained unchanged.

[0075] Comparative Example 3-2

[0076] The dosage of the prototype diclofenac and diclofenac sodium in Example 3 was reduced by 90%, the dosage of hirudin was maintained at the original amount, and the others remained unchanged.

[0077] Example 4

[0078] 1) Dispersing a prototype amino chitosan with a small molecular weight, a prototype amino chitosan with a medium molecular weight, and hydroxypropyl cellulose Klucel JF with a molecular weight of about 120,000 Daltons in water, wherein the prototype amino chitosan with a small molecular weight has a molecular weight of 1000-5000 Daltons, and its concentration is 12% wt / wt (based on 100% of the final total amount, i.e., 12 parts per 100 parts by weight in the end), the prototype amino chitosan with a medium molecular weight has a molecular weight of 10000-50000 Daltons, and its concentration is 8% wt / wt (based on 100% of the final total amount, i.e., 8 parts per 100 parts by weight in the end), and the hydroxypropyl cellulose has a concentration of 4% wt / wt (based on 100% of the final total amount, i.e., 4 parts per 100 parts by weight in the end), to obtain liquid A;

[0079] 2) Adding prototype diclofenac and nanometer-scale powder of hirudin or its aqueous dispersion to liquid A, wherein the (molar) amount of diclofenac is 0.98-1 times the (molar) amount of the amino group in the amino polysaccharide, and the weight ratio of the hirudin to the diclofenac is 1:100, mixing, and placing at room temperature for 12-24 hours to obtain liquid B;

[0080] 3) Add diclofenac sodium and hirudin to liquid B, wherein the weight of diclofenac sodium and hirudin is 0.5 times the weight of the above-mentioned prototype diclofenac and hirudin, respectively, and mix well to obtain liquid C;

[0081] 3) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 2% wt / wt (based on the final total amount of 100%, i.e., 2 parts per 100 parts by weight) to obtain liquid D;

[0082] 4) Adding an aqueous solution of collagen and an aqueous solution of heme peroxidase to liquid D respectively, wherein the concentration of the above collagen is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 weight parts in the end), and the ratio of the amount of the above heme peroxidase to the above collagen is 8 U / g. After mixing evenly, the temperature is maintained at 0°C to 4°C for 24-72 hours to make the collagen basically cross-linked, thereby obtaining liquid E;

[0083] 5) Liquid E was placed in a container so that the liquid layer thickness was 1.2 mm, and freeze-dried to remove the solvent.

[0084] Comparative Example 4

[0085] The method described in step 4) of Example 4 was changed to the following, and the rest remained unchanged:

[0086] Separately take the same volume of collagen aqueous solution and heme peroxidase aqueous solution as in Example 4, wherein the amount of the above collagen and the above heme peroxidase is the same as in Example 4, mix them evenly, maintain the temperature at 0°C to 4°C for 72 hours to allow the collagen to be basically cross-linked, and then add them to colloidal solution D, and mix them evenly to obtain colloidal solution E.

[0087] Example 5

[0088] 1) Dispersing a prototype amino chitosan with a small molecular weight, a prototype amino chitosan with a medium molecular weight, and hydroxypropyl cellulose Klucel JF with a molecular weight of about 120,000 Daltons in water, wherein the prototype amino chitosan with a small molecular weight has a molecular weight of 1000-5000 Daltons, and its concentration is 18% wt / wt (based on 100% of the final total amount, i.e., 18 parts per 100 parts by weight), the prototype amino chitosan with a medium molecular weight has a molecular weight of 10000-50000 Daltons, and its concentration is 8% wt / wt (based on 100% of the final total amount, i.e., 8 parts per 100 parts by weight), and the hydroxypropyl cellulose has a concentration of 4% wt / wt (based on 100% of the final total amount, i.e., 4 parts per 100 parts by weight), to obtain liquid A;

[0089] 2) Adding prototype diclofenac and nanometer-scale powder of hirudin or its aqueous dispersion to liquid A, wherein the (molar) amount of diclofenac is 0.98-1 times the (molar) amount of the amino group in the amino polysaccharide, and the weight ratio of the hirudin to the diclofenac is 1:100, mixing, and placing at room temperature for 12-24 hours to obtain liquid B;

[0090] 3) Add diclofenac sodium and hirudin to liquid B, wherein the weight of diclofenac sodium and hirudin is 0.5 times the weight of the above-mentioned prototype diclofenac and hirudin, respectively, and mix well to obtain liquid C;

[0091] 3) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 2% wt / wt (based on the final total amount of 100%, i.e., 2 parts per 100 parts by weight) to obtain liquid D;

[0092] 4) Adding an aqueous solution of collagen and an aqueous solution of heme peroxidase to liquid D respectively, wherein the concentration of the above collagen is 6% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 weight parts in the end), and the ratio of the amount of the above heme peroxidase to the above collagen is 8 U / g. After mixing evenly, the temperature is maintained at 0°C to 4°C for 24-72 hours to make the collagen basically cross-linked, thereby obtaining liquid E;

[0093] 5) Liquid E was placed in a container so that the liquid layer thickness was 1.2 mm, and freeze-dried to remove the solvent.

[0094] Comparative Example 5-1

[0095] The concentration of hydroxypropyl cellulose in Example 5 was changed from 4% wt / wt to 0.4% wt / wt, and the other contents remained unchanged.

[0096] Comparative Example 5-2

[0097] The concentration of hydroxypropyl cellulose in Example 5 was changed from 4% wt / wt to 12% wt / wt, and the other contents remained unchanged.

[0098] The method of the above prototype amino chitosan is as follows:

[0099] Dissolve the commercially available chitosan with a molecular weight of 100,000-500,000 Daltons and a deacetylation degree of not less than 95% in a three-necked flask with 2-5% acetic acid, heat in a water bath to 60-70°C, add H2O2 at a uniform rate while stirring to a concentration of 3-6%, keep warm and react for 4-6 hours, then add 5% sodium hydroxide solution to the reaction solution, adjust the pH to 4-6, and successively use pore sizes of 250,000 Daltons, 100,000 Daltons, 50,000 Daltons, 10,000 Daltons, and 50,000 Daltons. , 1000 Dalton, 500 Dalton, 100 Dalton nanofiltration membrane (ultrafiltration membrane), intercepting the solution of deacetylated chitosan with molecular weight of 100,000 Dalton-250,000 Dalton, 10,000 Dalton-50,000 Dalton, 1000 Dalton-5000 Dalton, and 100 Dalton-500 Dalton; then neutralizing to neutrality (pH=7), adding acetone with a volume twice that of the reactant dropwise under stirring, leaving overnight, filtering out the degradation product, washing with acetone, and drying under reduced pressure.

[0100] Test Example 1

[0101] The samples of the embodiment and the control example were cut into 2CM×1.5CM implant sponges and sterilized by γ-ray irradiation.

[0102] Animal in vivo toxicity tests, cytotoxicity tests, pyrogen tests, hemolysis tests, and intradermal injection experiments have shown that the implantable sponge is non-toxic, non-hemolytic, non-irritating, does not contain pyrogenic substances, has stable performance, and has good biocompatibility.

[0103] The sponge samples of the above embodiments and control examples are implanted at the same time after the apical cyst removal to treat the apical cyst.

[0104] 882 patients with apical cysts were randomly divided into one experimental group and two control groups, with 294 cases in each group. After the apical cyst was removed, the sponges of the embodiment and the control sample were implanted in each group. After the implantation, the mucoperiosteum was repaired, the wound was sutured conventionally, and pressure bandage was applied. Antibiotics were used to prevent infection after surgery, and the sutures were removed after 7 days.

[0105] The patients were observed 1 week, 1, 3, and 6 months after surgery, and the treatment effect was recorded 6 months after surgery. Efficacy criteria: cured: X-ray showed that the apical shadow disappeared, the affected tooth was not loose, there was no percussion pain, and chewing returned to normal; improved: X-ray showed that the apical shadow was reduced or basically disappeared, the chewing function basically returned to normal, the affected tooth was slightly loose, the pain disappeared, and there was occasional slight discomfort; uncured: the apical area continued to swell or paralysis, the cyst recurred, the affected tooth was loose, the pain was unbearable, and all symptoms were not significantly improved, or even aggravated.

[0106] Cure rate = number of cured cases / total number of cases × 100%.

[0107] Failure rate = number of failed cases / total number of cases × 100%.

[0108] The results are shown in Table 1.

[0109] Table 1-1 Clinical experimental results of Example 1 and its control sample for the treatment of apical cysts

[0110] Group Number of failures Number of cases improved Number of cured cases Cure rate (%) Failure rate (%) Example 1 8 25 261 88.8 2.7 Comparative Example 1-1 27 112 155 52.7 9.2 Comparative Example 1-2 56 35 203 69.0 19.0

[0111] Table 1-2 Clinical experimental results of Example 2 and its control sample for the treatment of apical cysts

[0112] Group Number of failures Number of cases improved Number of cured cases Cure rate (%) Failure rate (%) Example 2 14 28 252 85.7 4.8 Comparative Example 2-1 63 36 195 66.3 21.4 Comparative Example 2-2 24 102 168 57.1 8.2

[0113] Table 1-3 Clinical experimental results of Example 3 and its control sample for treating apical cysts

[0114] Group Number of failures Number of cases improved Number of cured cases Cure rate (%) Failure rate (%) Example 3 16 28 250 85.0 5.44 Comparative Example 3-1 69 77 148 50.3 23.5 Comparative Example 3-2 83 88 123 55.6 28.2

[0115] Table 1-4 Clinical experimental results of Example 4 and its control sample for treating apical cysts

[0116] Group Number of failures Number of cases improved Number of cured cases Cure rate (%) Failure rate (%) Example 4 12 32 250 85.0 4.1 Comparative Example 4 58 49 187 63.6 19.7

[0117] Table 1-5 Clinical experimental results of Example 5 and its control sample for the treatment of apical cysts

[0118] Group Number of failures Number of cases improved Number of cured cases Cure rate (%) Failure rate (%) Example 5 15 40 239 81.3 5.1 Comparative Example 5-1 79 89 126 42.8 26.8 Comparative Example 5-2 65 78 151 51.4 22.1

[0119] The results showed that the cure rate of the example group was significantly higher than that of the control group, and the failure rate of the example group was significantly lower than that of the control group. The example has better drug release performance and a moderate drug release rate. The control example releases the drug too slowly or too quickly. Too slow drug release affects the overall efficacy and makes the efficacy low; too fast drug release leads to a low blood drug concentration in the later stage, which significantly reduces the efficacy in the later stage and significantly increases the side effects in the early stage.

[0120] Test Example 2

[0121] The examples and control examples were implanted in the bone defect area after the surgery in 666 cases of tooth extraction, 504 cases of apical capsule extraction, 583 cases of periodontitis flap surgery, 356 cases of apex resection, 366 cases of superior sinus perforation repair, 381 cases of dead bone extraction, and 354 cases of alveolar plasty (implantation sponges cut into 2CM×1.5CM).

[0122] (1) Evaluation of analgesic effect: The visual analogue scale (VAS) of pain in the embodiment and control groups was calculated at rest and in motion 1 day, 2 days, and 3 days after surgery, respectively. No pain was scored as 0, sleep disturbance as 5, and severe pain as 10. The higher the score, the more severe the pain.

[0123] (2) Evaluation of anti-inflammatory effect: Record and count the adverse events of inflammation such as tissue redness and swelling that occurred during the entire clinical trial. Inflammation incidence rate = number of subjects with inflammation / number of subjects × 100%.

[0124] (3) Evaluation of antipyretic effect: Record and count the adverse events of fever in the subjects during the entire clinical trial. Fever incidence rate = number of subjects with fever / number of subjects × 100%.

[0125] The VAS score results of the subjects after receiving the sample treatment are shown in Table 2.

[0126] Table 3 shows the incidence of inflammation in the subjects before and 2, 4 and 7 days after treatment with the samples.

[0127] Table 4 shows the results of the incidence of fever in the subjects before and 2, 4 and 7 days after the sample treatment.

[0128] Table 2-1 VAS score results of the subjects in Example 2 and its control example after receiving sample treatment

[0129] 1 day 2 days 3 days Example 2 2.46±0.43 2.93±0.53 3.53±0.65 Comparative Example 2-1 2.05±0.41 3.23±0.62 4.04±0.68 Comparative Example 2-2 2.97±0.52 3.95±0.78 4.68±0.63

[0130] Table 2-2 VAS score results of the subjects in Example 3 and its control example after receiving sample treatment

[0131]

[0132]

[0133] Table 2-3 VAS score results of the subjects in Example 4 and its control example after receiving sample treatment

[0134] 1 day 2 days 3 days Example 4 2.39±0.42 2.83±0.51 3.41±0.58 Comparative Example 4 1.85±0.36 3.07±0.54 4.07±0.63

[0135] Table 2-4 VAS score results of the subjects in Example 5 and its control example after receiving sample treatment

[0136] 1 day 2 days 3 days Example 5 2.41±0.42 2.83±0.54 3.37±0.64 Comparative Example 5-1 2.55±0.48 3.39±0.57 4.24±0.65 Comparative Example 5-2 2.93±0.52 3.95±0.62 5.12±0.73

[0137] The results showed that the embodiments had better analgesic properties than the control examples.

[0138] Table 3-1 Inflammation incidence rate of subjects in Example 2 and its control example 2, 4 and 7 days after treatment

[0139] 2 days 4 days 7 days Example 2 19‰ 13‰ 6‰ Comparative Example 2-1 22‰ 20‰ 19‰ Comparative Example 2-2 64‰ 48‰ 34‰

[0140] Table 3-2 Inflammation incidence results of subjects in Example 3 and its control example 2 days, 4 days and 7 days after treatment

[0141] 2 days 4 days 7 days Example 3 17‰ 12‰ 7‰ Comparative Example 3-1 32‰ 25‰ 16‰ Comparative Example 3-2 55‰ 43‰ 31‰

[0142] Table 3-3 Inflammation incidence results of subjects in Example 4 and its control example 2 days, 4 days and 7 days after treatment

[0143] 2 days 4 days 7 days Example 4 21‰ 13‰ 6‰ Comparative Example 4 19‰ 16‰ 13‰

[0144] Table 3-4 Inflammation incidence results of subjects in Example 5 and its control example 2 days, 4 days and 7 days after treatment

[0145] 2 days 4 days 7 days Example 5 14‰ 10‰ 5‰ Comparative Example 5-1 20‰ 16‰ 12‰ Comparative Example 5-2 45‰ 38‰ 30‰

[0146] The results show that the embodiments have better anti-inflammatory properties than the control examples.

[0147] Table 4-1 Results of the incidence of fever in the subjects of Example 2 and its control example 2, 4 and 7 days after treatment

[0148] 2 days 4 days 7 days Example 2 18‰ 10‰ 4‰ Comparative Example 2-1 17‰ 15‰ 11‰ Comparative Example 2-2 53‰ 41‰ 38‰

[0149] Table 4-2 Results of the incidence of fever in the subjects of Example 3 and its control example 2, 4 and 7 days after treatment

[0150] 2 days 4 days 7 days Example 3 13‰ 8‰ 3‰ Comparative Example 3-1 25‰ 18‰ 12‰ Comparative Example 3-2 63‰ 51‰ 38‰

[0151] Table 4-3 Results of the incidence of fever in the subjects of Example 4 and its control example 2, 4 and 7 days after treatment

[0152]

[0153]

[0154] Table 4-4 Results of the incidence of fever in the subjects of Example 5 and its control example 2, 4 and 7 days after treatment

[0155] 2 days 4 days 7 days Example 5 17‰ 11‰ 6‰ Comparative Example 5-1 20‰ 17‰ 13‰ Comparative Example 5-2 61‰ 48‰ 36‰

[0156] The results show that the embodiment has better antipyretic performance than the control example.

[0157] The embodiment has better drug release performance, moderate drug release speed, better curative effect in pain relief, inflammation elimination, anti-fever, etc. The control example releases the drug too slowly or too quickly. The slow release affects the overall curative effect, making the curative effect low; the drug release is too fast, the blood drug concentration in the later stage is low, and the curative effect in the later stage is significantly reduced.

Claims

1. A method for preparing a sponge implant having rapid and long-term analgesic, anti-inflammatory, antipyretic and wound healing effects, the method comprising: 1) Dispersing a prototype amino chitosan with a small molecular weight, a prototype amino chitosan with a medium molecular weight, and a hydroxypropyl cellulose with a molecular weight of about 100,000-200,000 Daltons in water, wherein the prototype amino chitosan with a small molecular weight has a molecular weight of 1,000-5,000 Daltons and a concentration of 10-20% wt / wt, i.e., it contains 10-20 parts per 100 parts by weight, the prototype amino chitosan with a molecular weight of 10,000-50,000 Daltons and a concentration of 5-10% wt / wt, i.e., it contains 5-10 parts per 100 parts by weight, and the hydroxypropyl cellulose has a concentration of 3-6% wt / wt, i.e., it contains 3-6 parts per 100 parts by weight, to obtain liquid A; 2) Adding prototype diclofenac and nanometer-scale powder of hirudin or its aqueous dispersion to liquid A, wherein the molar amount of diclofenac is 0.95-1 times the molar amount of the amino group in the aminochitosan, and the weight ratio of the hirudin to the diclofenac is 1:50-200, mixing, and placing at room temperature for 12-24 hours to obtain liquid B; 3) Add diclofenac sodium and hirudin to liquid B, wherein the weight of diclofenac sodium and hirudin is 0.3-0.8 times the weight of the above-mentioned prototype diclofenac and hirudin, respectively, and mix well to obtain liquid C; 4) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 1-5% wt / wt, i.e., 1-5 parts per 100 parts by weight, to obtain liquid D; 5) Adding an aqueous solution of collagen and an aqueous solution of heme peroxidase to liquid D respectively, wherein the concentration of the above collagen is 1-6% wt / wt, i.e., 1-6 parts are contained in every 100 parts by weight, and the ratio of the amount of the above heme peroxidase to the above collagen is 1-15 U / g. After mixing evenly, the temperature is maintained at 0°C to 4°C for 24-72 hours to make the collagen basically cross-linked, thereby obtaining liquid E; 6) Liquid E is placed in a container so that the liquid layer thickness is 1-2 mm, and freeze-dried to remove the solvent.

2. The preparation method according to claim 1, characterized in that The concentration of the small molecular weight prototype aminoglycan is 13-17% wt / wt.

3. The preparation method according to claim 1, characterized in that The concentration of the intermediate molecular weight prototype amino polysaccharide is 6-8% wt / wt.

4. The preparation method according to claim 1, characterized in that The concentration of the hydroxypropyl cellulose is 4-5% wt / wt.

5. The preparation method according to claim 1, characterized in that The molar amounts of the diclofenac and hirudin sodium are 0.4-0.6 times the molar amounts of the prototype diclofenac and hirudin, respectively.

6. The preparation method according to claim 1, characterized in that The concentration of the cross-linked sodium hyaluronate is 2-4% wt / wt.

7. The preparation method according to claim 1, characterized in that The concentration of the collagen is 3-4% wt / wt.

8. The preparation method according to claim 1, characterized in that The ratio of the amount of the glutamyl endopeptidase to the amount of the collagen is 3-10 U / g.

9. The preparation method according to claim 1, characterized in that The thickness of the liquid layer is 1.3-1.8 mm.

10. The preparation method according to claim 1, characterized in that The preparation method also includes further preparing the sponge implant into a film, column, strip, plate, block, plug, pill, sheet, sponge or gel.